Protecting the Kidney in Liver Transplant Recipients: Practice‐Based Recommendations From the American Society of Transplantation Liver and Intestine Community of Practice. Issue 9 (22nd April 2016) - Levitsky, J.; O'Leary, J. G.; Asrani, S.; Sharma, P.; Fung, J.; Wiseman, A.; Niemann, C. U.
Abstract : Both acute and chronic kidney disease are common after liver transplantation and result in significant morbidity and mortality. The introduction of the Model for End‐stage Liver Disease score has directly correlated with an increased prevalence of perioperative renal dysfunction and the number of simultaneous liver–kidney transplantations performed. Kidney dysfunction in this population is typically multifactorial and related to preexisting conditions, pretransplantation renal injury, perioperative events, and posttransplantation nephrotoxic immunosuppressive therapies. The management of kidney disease after liver transplantation is challenging, as by the time the serum creatinine level is significantly elevated, few interventions affect the course of progression. Also, immunological factors such as antibody‐mediated kidney rejection have become of greater interest given the rising liver–kidney transplant population. Therefore, this review, assembled by experts in the field and endorsed by the American Society of Transplantation Liver and Intestine Community of Practice, provides a critical assessment of measures of renal function and interventions aimed at preserving renal function early and late after liver and simultaneous liver–kidney transplantation. Key points and practice‐based recommendations for the prevention and management of kidney injury in this population are provided to offer guidance for clinicians and identify gaps in knowledge for future investigations. Abstract : This review summarizes key data and provides practice‐based guidelines to assess and preserve renal function early and late after liver and liver–kidney transplantation. See page 2516 for the companion review.